Surface electromyographic characteristics of lower limb muscles in frail older adults: Protocol for an observational case - control study - Pingping Huang; Linjing Wu; Shiqi Chen; Jiahua Li; Yu Zhang; Yuan Chen (PLoS ONE, 2025)
Background Frailty is a dynamic and reversible clinical syndrome in older adults that profoundly affects an individual’s quality of life, health outcomes, and overall prognosis, thereby underscoring the importance of early identification and timely intervention. Alterations in the biomechanical parameters of lower limb muscles may constitute the pathophysiological underpinnings of frailty. Surface electromyography (sEMG) is a vital tool for assessing neuromuscular function. To date, there are no reports on the characteristics of surface electromyographic in the lower limbs of frail older individuals. Methods This is an observational category matching case-control study. We aim to recruit 75 frail older adults and 75 matched non-frail older participants (1:1), to be assigned respectively to the case and control groups. All subjects will undergo sEMG of the lower limb muscles during a 10-meter walk test and will be assessed for gait and balance. The primary outcome will be the difference in sEMG parameters between the two groups, including root mean square (RMS), integrated electromyography (IEMG), averaged electromyography (AEMG), mean power frequency (MPF), and median frequency (MF), as well as those computed from these metrics, including symmetry index (SI), muscle activation sequences, and muscle contribution rates. Secondary outcomes will encompass the time taken to complete the 10-meter walk test and assessments of gait and balance. Furthermore, the relationship between electromyographic parameters and the state of frailty will be evaluated, and the predictive capability of these sEMG parameters for identifying frailty will be explored. Trial registration number ChiCTR2300078953